---------------------------------------------------------------------------------------------------- --- Copyright (c) 2014 Parikshit Khanna. All rights reserved. --- Released under Apache 2.0 license as described in the file LICENSE. --- Authors: Parikshit Khanna, Jeremy Avigad ---------------------------------------------------------------------------------------------------- -- Theory list -- =========== -- -- Basic properties of lists. import tactic import nat using nat using eq_proofs namespace list -- Type -- ---- inductive list (T : Type) : Type := | nil {} : list T | cons : T → list T → list T infix `::` : 65 := cons section variable {T : Type} theorem list_induction_on {P : list T → Prop} (l : list T) (Hnil : P nil) (Hind : forall x : T, forall l : list T, forall H : P l, P (cons x l)) : P l := list_rec Hnil Hind l theorem list_cases_on {P : list T → Prop} (l : list T) (Hnil : P nil) (Hcons : forall x : T, forall l : list T, P (cons x l)) : P l := list_induction_on l Hnil (take x l IH, Hcons x l) notation `[` l:(foldr `,` (h t, cons h t) nil) `]` := l notation `[` `]` := nil -- TODO: should this be needed? notation `[` x `]` := cons x nil -- Concat -- ------ definition concat (s t : list T) : list T := list_rec t (fun x : T, fun l : list T, fun u : list T, cons x u) s infixl `++` : 65 := concat theorem nil_concat (t : list T) : nil ++ t = t := refl _ theorem cons_concat (x : T) (s t : list T) : (x :: s) ++ t = x :: (s ++ t) := refl _ theorem concat_nil (t : list T) : t ++ nil = t := list_induction_on t (refl _) (take (x : T) (l : list T) (H : concat l nil = l), show concat (cons x l) nil = cons x l, from H ▸ refl _) -- TODO: these work: -- calc -- concat (cons x l) nil = cons x (concat l nil) : refl (concat (cons x l) nil) -- ... = cons x l : {H}) -- H ▸ (refl (cons x (concat l nil)))) -- doesn't work: -- H ▸ (refl (concat (cons x l) nil))) theorem concat_assoc (s t u : list T) : s ++ t ++ u = s ++ (t ++ u) := list_induction_on s (refl _) (take x l, assume H : concat (concat l t) u = concat l (concat t u), calc concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : refl _ ... = cons x (concat l (concat t u)) : { H } ... = concat (cons x l) (concat t u) : refl _) -- TODO: deleting refl doesn't work, nor does -- H ▸ refl _) -- concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : refl _ -- ... = concat (cons x l) (concat t u) : { H }) -- concat (concat (cons x l) t) u = cons x (concat l (concat t u)) : { H } -- ... = concat (cons x l) (concat t u) : refl _) -- concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : refl _ -- ... = cons x (concat l (concat t u)) : { H } -- ... = concat (cons x l) (concat t u) : refl _) -- add_rewrite nil_concat cons_concat concat_nil concat_assoc -- Length -- ------ definition length : list T → ℕ := list_rec 0 (fun x l m, succ m) -- TODO: cannot replace zero by 0 theorem length_nil : length (@nil T) = zero := refl _ theorem length_cons (x : T) (t : list T) : length (x :: t) = succ (length t) := refl _ theorem length_concat (s t : list T) : length (s ++ t) = length s + length t := list_induction_on s (calc length (concat nil t) = length t : refl _ ... = zero + length t : {symm (add_zero_left (length t))} ... = length (@nil T) + length t : refl _) (take x s, assume H : length (concat s t) = length s + length t, calc length (concat (cons x s) t ) = succ (length (concat s t)) : refl _ ... = succ (length s + length t) : { H } ... = succ (length s) + length t : {symm (add_succ_left _ _)} ... = length (cons x s) + length t : refl _) -- -- add_rewrite length_nil length_cons -- Reverse -- ------- definition reverse : list T → list T := list_rec nil (fun x l r, r ++ [x]) theorem reverse_nil : reverse (@nil T) = nil := refl _ theorem reverse_cons (x : T) (l : list T) : reverse (x :: l) = (reverse l) ++ (cons x nil) := refl _ -- opaque_hint (hiding reverse) theorem reverse_concat (s t : list T) : reverse (s ++ t) = (reverse t) ++ (reverse s) := list_induction_on s (calc reverse (concat nil t) = reverse t : { nil_concat _ } ... = concat (reverse t) nil : symm (concat_nil _) ... = concat (reverse t) (reverse nil) : {symm (reverse_nil)}) (take x l, assume H : reverse (concat l t) = concat (reverse t) (reverse l), calc reverse (concat (cons x l) t) = concat (reverse (concat l t)) (cons x nil) : refl _ ... = concat (concat (reverse t) (reverse l)) (cons x nil) : { H } ... = concat (reverse t) (concat (reverse l) (cons x nil)) : concat_assoc _ _ _ ... = concat (reverse t) (reverse (cons x l)) : refl _) theorem reverse_reverse (l : list T) : reverse (reverse l) = l := list_induction_on l (refl _) (take x l', assume H: reverse (reverse l') = l', show reverse (reverse (cons x l')) = cons x l', from calc reverse (reverse (cons x l')) = concat (reverse (cons x nil)) (reverse (reverse l')) : {reverse_concat _ _} ... = cons x l' : {H}) -- longer versions: -- reverse (reverse (cons x l)) = -- concat (reverse (cons x nil)) (reverse (reverse l)) : {reverse_concat _ _} -- ... = concat (reverse (cons x nil)) l : {H} -- ... = cons x l : refl _) -- calc -- reverse (reverse (cons x l)) = reverse (concat (reverse l) (cons x nil)) -- : refl _ -- ... = concat (reverse (cons x nil)) (reverse (reverse l)) : {reverse_concat _ _} -- ... = concat (reverse (cons x nil)) l : {H} -- ... = cons x l : refl _) -- before: -- calc -- reverse (reverse (cons x l)) = reverse (concat (reverse l) (cons x nil)) -- : {reverse_cons x l} -- ... = concat (reverse (cons x nil)) (reverse (reverse l)) : {reverse_concat _ _} -- ... = concat (reverse (cons x nil)) l : {H} -- ... = concat (concat (reverse nil) (cons x nil)) l : {reverse_cons _ _} -- ... = concat (concat nil (cons x nil)) l : {reverse_nil} -- ... = concat (cons x nil) l : {nil_concat _} -- ... = cons x (concat nil l) : cons_concat _ _ _ -- ... = cons x l : {nil_concat _}) -- Append -- ------ -- TODO: define reverse from append definition append (x : T) : list T → list T := list_rec (x :: nil) (fun y l l', y :: l') theorem append_nil (x : T) : append x nil = [x] := refl _ theorem append_cons (x : T) (y : T) (l : list T) : append x (y :: l) = y :: (append x l) := refl _ theorem append_eq_concat (x : T) (l : list T) : append x l = l ++ [x] := list_induction_on l (refl _) (take y l, assume P : append x l = concat l [x], P ▸ refl _) -- calc -- append x (cons y l) = concat (cons y l) (cons x nil) : { P }) -- calc -- append x (cons y l) = cons y (concat l (cons x nil)) : { P } -- ... = concat (cons y l) (cons x nil) : refl _) -- here it works! -- append x (cons y l) = cons y (append x l) : refl _ -- ... = cons y (concat l (cons x nil)) : { P } -- ... = concat (cons y l) (cons x nil) : refl _) theorem append_eq_reverse_cons (x : T) (l : list T) : append x l = reverse (x :: reverse l) := list_induction_on l (calc append x nil = [x] : (refl _) ... = concat nil [x] : {symm (nil_concat _)} ... = concat (reverse nil) [x] : {symm (reverse_nil)} ... = reverse [x] : {symm (reverse_cons _ _)} ... = reverse (x :: (reverse nil)) : {symm (reverse_nil)}) (take y l', assume H : append x l' = reverse (x :: reverse l'), calc append x (y :: l') = (y :: l') ++ [ x ] : append_eq_concat _ _ ... = concat (reverse (reverse (y :: l'))) [ x ] : {symm (reverse_reverse _)} ... = reverse (x :: (reverse (y :: l'))) : refl _) -- Head and tail -- ------------- definition head (x0 : T) : list T → T := list_rec x0 (fun x l h, x) theorem head_nil (x0 : T) : head x0 (@nil T) = x0 := refl _ theorem head_cons (x : T) (x0 : T) (t : list T) : head x0 (x :: t) = x := refl _ theorem head_concat (s t : list T) (x0 : T) : s ≠ nil → (head x0 (s ++ t) = head x0 s) := list_cases_on s (take H : nil ≠ nil, absurd_elim (head x0 (concat nil t) = head x0 nil) (refl nil) H) (take x s, take H : cons x s ≠ nil, calc head x0 (concat (cons x s) t) = head x0 (cons x (concat s t)) : {cons_concat _ _ _} ... = x : {head_cons _ _ _} ... = head x0 (cons x s) : {symm ( head_cons x x0 s)}) definition tail : list T → list T := list_rec nil (fun x l b, l) theorem tail_nil : tail (@nil T) = nil := refl _ theorem tail_cons (x : T) (l : list T) : tail (cons x l) = l := refl _ theorem cons_head_tail (x0 : T) (l : list T) : l ≠ nil → (head x0 l) :: (tail l) = l := list_cases_on l (assume H : nil ≠ nil, absurd_elim _ (refl _) H) (take x l, assume H : cons x l ≠ nil, refl _) -- List membership -- --------------- definition mem (f : T) : list T → Prop := list_rec false (fun x l H, (H ∨ (x = f))) infix `∈` : 50 := mem theorem mem_nil (f : T) : mem f nil ↔ false := iff_refl _ theorem mem_cons (x : T) (f : T) (l : list T) : mem f (cons x l) ↔ (mem f l ∨ x = f) := iff_refl _ -- TODO: fix this! -- theorem or_right_comm : ∀a b c, (a ∨ b) ∨ c ↔ (a ∨ c) ∨ b := -- take a b c, calc -- (a ∨ b) ∨ c ↔ a ∨ (b ∨ c) : or_assoc _ _ _ -- ... ↔ a ∨ (c ∨ b) : {or_comm _ _} -- ... ↔ (a ∨ c) ∨ b : (or_assoc _ _ _)⁻¹ -- theorem mem_concat_imp_or (f : T) (s t : list T) : mem f (concat s t) → mem f s ∨ mem f t := -- list_induction_on s -- (assume H : mem f (concat nil t), -- have H1 : mem f t, from subst H (nil_concat t), -- show mem f nil ∨ mem f t, from or_intro_right _ H1) -- (take x l, -- assume IH : mem f (concat l t) → mem f l ∨ mem f t, -- assume H : mem f (concat (cons x l) t), -- have H1 : mem f (cons x (concat l t)), from subst H (cons_concat _ _ _), -- have H2 : mem f (concat l t) ∨ x = f, from (mem_cons _ _ _) ◂ H1, -- have H3 : (mem f l ∨ mem f t) ∨ x = f, from imp_or_left H2 IH, -- have H4 : (mem f l ∨ x = f) ∨ mem f t, from or_right_comm _ _ _ ◂ H3, -- show mem f (cons x l) ∨ mem f t, from subst H4 (symm (mem_cons _ _ _))) -- theorem mem_or_imp_concat (f : T) (s t : list T) : -- mem f s ∨ mem f t → mem f (concat s t) -- := -- list_induction_on s -- (assume H : mem f nil ∨ mem f t, -- have H1 : false ∨ mem f t, from subst H (mem_nil f), -- have H2 : mem f t, from subst H1 (or_false_right _), -- show mem f (concat nil t), from subst H2 (symm (nil_concat _))) -- (take x l, -- assume IH : mem f l ∨ mem f t → mem f (concat l t), -- assume H : (mem f (cons x l)) ∨ (mem f t), -- have H1 : ((mem f l) ∨ (x = f)) ∨ (mem f t), from subst H (mem_cons _ _ _), -- have H2 : (mem f t) ∨ ((mem f l) ∨ (x = f)), from subst H1 (or_comm _ _), -- have H3 : ((mem f t) ∨ (mem f l)) ∨ (x = f), from subst H2 (symm (or_assoc _ _ _)), -- have H4 : ((mem f l) ∨ (mem f t)) ∨ (x = f), from subst H3 (or_comm _ _), -- have H5 : (mem f (concat l t)) ∨ (x = f), from (or_imp_or_left H4 IH), -- have H6 : (mem f (cons x (concat l t))), from subst H5 (symm (mem_cons _ _ _)), -- show (mem f (concat (cons x l) t)), from subst H6 (symm (cons_concat _ _ _))) -- theorem mem_concat (f : T) (s t : list T) : mem f (concat s t) ↔ mem f s ∨ mem f t -- := iff_intro (mem_concat_imp_or _ _ _) (mem_or_imp_concat _ _ _) -- theorem mem_split (f : T) (s : list T) : -- mem f s → ∃ a b : list T, s = concat a (cons f b) -- := -- list_induction_on s -- (assume H : mem f nil, -- have H1 : mem f nil ↔ false, from (mem_nil f), -- show ∃ a b : list T, nil = concat a (cons f b), from absurd_elim _ H (eqf_elim H1)) -- (take x l, -- assume P1 : mem f l → ∃ a b : list T, l = concat a (cons f b), -- assume P2 : mem f (cons x l), -- have P3 : mem f l ∨ x = f, from subst P2 (mem_cons _ _ _), -- show ∃ a b : list T, cons x l = concat a (cons f b), from -- or_elim P3 -- (assume Q1 : mem f l, -- obtain (a : list T) (PQ : ∃ b, l = concat a (cons f b)), from P1 Q1, -- obtain (b : list T) (RS : l = concat a (cons f b)), from PQ, -- exists_intro (cons x a) -- (exists_intro b -- (calc -- cons x l = cons x (concat a (cons f b)) : { RS } -- ... = concat (cons x a) (cons f b) : (symm (cons_concat _ _ _))))) -- (assume Q2 : x = f, -- exists_intro nil -- (exists_intro l -- (calc -- cons x l = concat nil (cons x l) : (symm (nil_concat _)) -- ... = concat nil (cons f l) : {Q2})))) -- -- Find -- -- ---- -- definition find (x : T) : list T → ℕ -- := list_rec 0 (fun y l b, if x = y then 0 else succ b) -- theorem find_nil (f : T) : find f nil = 0 -- :=refl _ -- theorem find_cons (x y : T) (l : list T) : find x (cons y l) = -- if x = y then 0 else succ (find x l) -- := refl _ -- theorem not_mem_find (l : list T) (x : T) : ¬ mem x l → find x l = length l -- := -- @list_induction_on T (λl, ¬ mem x l → find x l = length l) l -- -- list_induction_on l -- (assume P1 : ¬ mem x nil, -- show find x nil = length nil, from -- calc -- find x nil = 0 : find_nil _ -- ... = length nil : by simp) -- (take y l, -- assume IH : ¬ (mem x l) → find x l = length l, -- assume P1 : ¬ (mem x (cons y l)), -- have P2 : ¬ (mem x l ∨ (y = x)), from subst P1 (mem_cons _ _ _), -- have P3 : ¬ (mem x l) ∧ (y ≠ x),from subst P2 (not_or _ _), -- have P4 : x ≠ y, from ne_symm (and_elim_right P3), -- calc -- find x (cons y l) = succ (find x l) : -- trans (find_cons _ _ _) (not_imp_if_eq P4 _ _) -- ... = succ (length l) : {IH (and_elim_left P3)} -- ... = length (cons y l) : symm (length_cons _ _)) -- -- nth element -- -- ----------- -- definition nth (x0 : T) (l : list T) (n : ℕ) : T -- := nat.rec (λl, head x0 l) (λm f l, f (tail l)) n l -- theorem nth (x0 : T) (l : list T) : nth_element x0 l 0 = head x0 l -- := hcongr1 (nat::rec_zero _ _) l -- theorem nth_element_succ (x0 : T) (l : list T) (n : ℕ) : -- nth_element x0 l (succ n) = nth_element x0 (tail l) n -- := hcongr1 (nat::rec_succ _ _ _) l -- end